The Effect Of Environmental Temperature In The Growth And Development Of Echinococcus granulosus (Batsch1786: Raad Harbi Rahif , Usama Ali Mardan Al-Naimi - Rahif, Raad Harbi (The Iraqi Journal of Veterinary Medicine, 2005)
The study highligthened on the effect of the field enviromental & controlledtempratures in the experimental infection with Echinococcus granulosus indogs, n = 6 local dogs, at the age of 1.5-3 months, were used . Each dog wasdosed with 8658 protoscoleces with 92.78% viability for 28 and 33 days postinfection (PI). Animals were subdivided into 2groups. Results denoted that thelow enviromental temperatures retarded the growth and development of E.granulosus.All tapeworms, isolated from the small intestine of dogs housedunder controlled temperatures, with the average of 21.85ºc(group1),had 3proglottids,whereas those isolated from dogs housed under field temperatures,with the average of 11.12ºc (group2) ,had only 2 proglottids.The average totallength of E. granulosus ,at the age of 28 days, isolated fromgroup1,was1.70±0.24mm,longer than those that isolated from group2,with theaverage length of 1.13±0.06mm.The average total length of E.granulosus ,at theage of 33 days , isolated from group 1 and 2 ,was 2.68±0.35 mm and 1.67±0.21,respectively . Significant statistical differences (p<0.05) were found in theaverage total length of E.granulosus isolated from both groups at different ages.Echinococcus granulosus isolated from group1 were found mature more thanthose isolated from group2,and the number of rostellar hooks of the former werealso more than those of the 2nd group, the number of rostellar hooks were, at theage of 33 days,were34.53±2.19 and29.47±0.62 for the 1st and 2nd gr